(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The aim of this paper is todemonstrate and discuss the role of normative awareness, participatory and gatekeeping assignments of organizational and entrepreneurial healthcarejournalists.’ Entrepreneurial journalism’ is a new exemplar. This new paradigmalso forces academic world to reconsider traditional methods in how to preparestudents for a career. Journalists need not sacrifice core values ofindependence, truth-telling and impartiality if they choose to become businessowners. ‘Entrepreneurial journalism’ also fits within the historical context ofcurriculum change and discuss within academe over how to adapt to newtechnologies.